Production and optimization of bioethanol from over ripen sour banana fruit wastes (Musa sapientum) using Saccharomyces cerevisiae - Vivekanandaraja, R.; Kapilan, R. (University of Jaffna, 2021)
This study was carried out to produce bioethanol from low quality over ripen Musa sapientum (sour banana) fruit wastes to enhance the yield of bioethanol. When the sour banana juice was inoculated with Saccharomyces cerevisiae (2 g/L) in the fermentation media (100 mL, 8o Brix) composed of 10 g/L yeast extract, 10 g/L KH2 PO4 , 2 g/L (NH4 )2 SO4 , 2 g/L peptone, and 0.5 g/L MgSO4 ·7H2 O and fermented for 24h at 30 °C and 100 rpm, the ethanol yield was 0.8% v/v. When nitrogen sources urea, ammonium sulphate, ammonium carbonate, and ammonium nitrate were used in the fermentation media (2.0 g/100mL), significantly higher ethanol yield (p<0.05, 0.90%) was produced with ammonium carbonate. When yeast inoculum was increased to 5 g/L, the ethanol yield was significantly higher (p<0.05, 1.00%, 1.11 times) than the control. When the temperature was 25 °C, the ethanol yield was significantly increased (p<0.05) by 1.2 times the control temperature of 30 °C. When the rotation speed was 150 rpm, the ethanol yield was significantly higher (p<0.05) than the control (100 rpm). Ethanol yield was significantly higher (p<0.05, .15 times - 4.10 %) with 90% of banana juice. With 0.1 g/100mL of ammonium carbonate, ethanol yield was significantly increased by 1.1 times (p<0.05, 40 %) than the non-optimized control (0.2 g/100mL). Sucrose significantly stimulated ethanol yield than the other sugars. Fifteen grams per hundred milliliters of sucrose yielded significantly higher ethanol (p<0.05, 2.33 times) than the non-optimized control (2 g/100mL). When the pH of the medium was optimized at 6.0, the ethanol yield was significantly higher (p<0.05, 12.60%). Therefore, Musa sapientum could be an effective substrate for bioethanol production and optimization process increased the bioethanol yield significantly by 15.75 times (12.60% - 1.6o Brix).
Keywords: Baker’s yeast; Bioethanol; Sour banana fruit waste; Fermentation; Incubation period